Menyadari Hikmah Masa Lalu: Jejak-Jejak Toleransi Beragama dalam Kekristenan sebelum Abad Pencerahan - Stau, Januarius Martin (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
This paper aims to provide an overview of religious tolerance as it relates directly or indirectly to Christianity before the Enlightenment. Religious tolerance in the context of pre-Enlightenment Christianity was complex and diverse, depending on the situation, time periodization, location or place, and socio-political context of the society. In Ancient Greece, political tolerance or intolerance of religion during the Hellenistic period rested on community and legal grounds, not on behavior. Whereas in ancient Rome the Hellenistic political tolerance of other religions and cults was adopted by the Romans, but by also adding some criteria centered on the civil, religious, and theological obedience of foreign gods and foreigners to the Dea Romana, the Senate, and the People of Rome. In the 4th century era of Constantine the Great, religious tolerance was realized with the issuance of the Edict of Milan, in 313, which proclaimed religious freedom in the Roman Empire. While in the 5th century era of Augustine of Hippo, religious tolerance was a careful judgment, driven by caritas. In the Middle Ages, religious tolerance took on a new form as interfaith dialogue, which was realised by including representatives of other religions in theological discourse.